G92(P) Ward to court – a novel safeguarding educational experience. (27th April 2016) - Pryde, K; Sykes, K; Roe, M; Fairhurst, J; Wheeler, R
Abstract : Aims: Safeguarding is an essential aspect of all paediatricians' work. It requires many skills including sensitive communication with family/carers; report writing and court appearances. Trainees need to gain knowledge of the multi-agency systems for assessing and managing such cases. However, these cases are often devolved to the senior doctor (consultant), limiting trainee's exposure. Methods: We created a novel educational intervention for senior paediatric trainees to address these training needs. Session 1 (1/2 day): A 10-month-old (moulaged manikin) was referred with a swelling on his head. X-ray identified a fracture. The trainees took a history from the parents (actors), examined the child, documented their findings and then explained the next steps to parents. Following scenario de-brief (including safeguarding education), a simulated multi-agency strategy meeting was convened, with trainees representing the medical team. Finally, all trainees wrote a safeguarding report. Session 2 (1/2 day): A moot family court scenario. A colleague (an experienced lawyer and consultant) and our local named doctor for child protection played the roles of advocates for the local authority and child respectively. Two trainees were witnesses; others were allocated roles including members of the bench, advocates for the parents, and advisers to the advocates. They were given time to 'prepare' for court. The witnesses were brought to the stand, sworn in, faced questioning and then cross-examined. Following the simulation we debriefed report writing, court preparation and taking the stand. Results: Trainees completed pre and post-simulation questionnaires on their understanding of processes and confidence in preparing for, and appearing in court for such cases. Statistically analysis showed significantly improved (p < 0.001) self-rated confidence post-simulation (see figure). Discussion: This novel intervention provided an opportunity for trainees to gain experience and confidence in managing safeguarding cases and appearing in court. A search of the literature found little evidence of similar methods being utilised elsewhere. We propose this is an excellent way to immerse trainees in high stakes situations prior to them 'doing it for real'. We plan to further enhance the fidelity of the court scenario by engaging our local university law students as advocates, which will benefit both groups of learners.